Electronic Litigation: Towards an Electronic Administrative Jurisdiction in the Kingdom of Saudi Arabia - Aljazi , Jehad Dhifallah (Dirasat: Shari’a and Law Sciences, 2021)
The importance of electronic means appeared in various aspects of human activity, including their importance in judicial notification procedures and other judicial procedures related to the lawsuit in general, including cases of Board of Grievances, which handles the administrative case in the kingdom of Saudi Arabia. The importance of electronic means in the scope of the administrative case was enhanced by the issuance of royal orders, such as the royal order, which includes the approval of the use of electronic means in judicial notifications, as well as the launch of Board of Grievances of the "Maeen Electronic" Program, which allows litigants to have the necessary access to the progress of their cases electronically. The researcher has come to the possibility of only holding trial sessions, completing administrative lawsuit procedures, and issuing judgments in administrative cases by electronic means. Electronic media, including computers and communication networks, are not considered to be mere means for taking all the procedures stipulated in the regulations to ensure a fair trial starting from the registration of the lawsuit, ending with the issuance of a final ruling in the dispute. The research recommends the need to allocate a place to testify in one of the headquarters of administrative courts scattered in Saudi cities, provided that it is under the supervision of the court, provided that the courts are equipped with electronic infrastructure that achieves this end.